Juvenile delinquency and the limits of Western influence, 1850 - 2000 - Ellis, Heather (Palgrave studies in the history of childhood, 2014)
"Juvenile Delinquency and the Limits of Western Influence, 1850-2000 brings together a wide range of case studies from across the globe, written by some of the leading scholars in the field, to explore the complex ways in which historical understandings of childhood and juvenile delinquency have been constructed in a global context. The book highlights the continued entanglement of historical descriptions of the development of juvenile justice systems in other parts of the world with narratives of Western colonialism and the persistence of notions of a cultural divide between East and West. It also stresses the need to combine theoretical insights from traditional comparative history with new global history approaches. In doing so, the case studies examined in the volume reveal the significant limitations to the influence of Western ideas about juvenile delinquency in other parts of the world, as well as the important degree to which Western understandings of delinquency were also constructed in a transnational context"--